Impact of High Molecular Weight Polymers on Viability, Metabolic Activity and Multilineage Differentiation Ability of Mesenchymal Stromal Cells Cryopreserved in Me2SO Absence - Mutsenko, Vitaliy V.; Rogulska, Elena Yu.; Tarusin, Dmitriy N.; Petrenko, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â  Probl Cryobiol Cryomed 2014; 24(2):164.